(untitled) (World Economics and Finance Bulletin, 2023)
The article describes the problems of scientific personnel and specialists in the agrarian sphere of our country. At the new stage of economic reforms, such changes are the main basis for the development of scientific personnel potential in increasing the effectiveness of research. It is necessary to ensure adequate improvement of scientific potential in scientific institutions, training of personnel in the field and improvement of professional skills related to their professional research. It is important to increase the share of doctors of science, to prepare specialists of excellent level in higher educational institutions, to increase the quality of scientific personnel, to use scientific potential effectively and to ensure the development of Agriculture in scientific terms.